Hispanicism in Chilean Women: Francoist Influences in the National Secretariat for Women (Chile 1973-1989) [el Hispanismo en Las Mujeres Chilenas: Las Influencias Franquistas en la Secretaría Nacional de la Mujer (Chile 1973-1989)] - Grez-Cook, F (Ariadna Ediciones, 2022)
The present article studies the collaboration between Spanish and Chilean regime from 1973 to 1989. It will analyze the influence from Hispanics ideas, through the Feminine Section (FS), to the creation and activities of the National Secretariat for Women (SNM). Throughout this paper it will be possible to see the institutional and ideologically collaboration done by Section Female, that certainly made the Hispanics thought one of the ideological influences in the project established in Chile. The transfer of Hispanic in our country helped to create a specific ideology on women that was promoted by officialdom. © 2022 Ariadna Ediciones. All rights reserved.